Non-dermatophytic onychomycosis caused by Fusarium spp. in a 58-year-old agricultural worker: a case report - Aminy, Sayyidah A.; Amaia, Devika N.; Soebono, Hardyanto; Nuryastuti, Titik (Journal of Clinical Microbiology and Infectious Diseases, 2024)
Introduction: Onychomycosis is a nail infection caused by dermatophytes, non-dermatophytes, and yeast. Fusarium spp. is one of the non-dermatophyte molds that can cause onychomycosis. A superficial infection with these fungi can lead to an invasive infection. Few case reports of onychomycosis caused by Fusarium spp. in Indonesia have been documented. Case description: We present a case of a 58-year-old male patient with a history of hepatitis B, atopic dermatitis, and corticosteroid consumption. Hyperkeratosis with a yellowish color was observed, and small particles of cornified material were discovered beneath both of his great toenails. Onychomycosis is assessed based on clinical symptoms. Mycological examinations were done by KOH examination and culture. Macroscopic examination of the culture revealed a white, cottony-looking mold with a non-pigmented reverse. Microscopic examination showed the septate hyphae, the canoe-shaped macroconidia, and the oval microconidia. We diagnosed onychomycosis caused by Fusarium spp. Based on macroscopic and microscopic examination. The antifungal susceptibility test showed a high MIC against several antifungal agents. Conclusion: It is important to be cautious for onychomycosis caused by Fusarium spp. infection as superficial infection can progress to invasive disease. Given the high prevalence of Fusarium spp. resistance to the antifungal group, antifungal treatment selection should be carefully considered.